The use of information and communication technology in the performance of ministries: a case of Public Sector of Zimbabwe - Mashumba, Phyllia (Midlands State University, 2014)
The purpose of the research was to make a survey of the use of Information and Communication Technology in the performance of ministries in the Public Sector of Zimbabwe with specific reference to the 5 selected Ministries .The backgrounds reviewed up to the global level of ICT. The proliferation of ICT indicates a low average due to insuffient budgets. The availability of ICT in ministries is not improving the performance of Ministries. There is lack of management support which result in low literacy rate in which the respondents indicated that the funds are not adequate and the selection criteria is not fair on training. There should be control and protection of Public secrets by harnessing ICT security. The study further included an exploratory quantitative component where a sample of fifty employees was selected to complete the questionnaires, 10 questionnaires were distributed to 10 heads of sections in Ministries. The recommendations made included the need to have an effective Management of Information Systems and training of staff, full support from management is needed in all areas including budget and this will result in the protection of the Nation secrets and keep Zimbabwe abreast in Technology.